A case of pan‐resistant Burkholderia cepacia complex bacteremic pneumonia, after lung transplantation treated with a targeted combination therapy. Issue 2 (1st January 2019) - Cantón‐Bulnes, María Luisa; Hurtado Martínez, Ángela; López‐Cerero, Lorena; Arenzana Seisdedos, Ángel; Merino‐Bohorquez, Vicente; Garnacho‐Montero, José
Abstract: We describe a case of one patient with cystic fibrosis who developed a pan‐resistant Burkholderia cepacia complex rapidly progressive bacteraemic pneunonia, following bilateral lung transplantation. The patient was treated with a targeted combination antibiotic therapy (meropenem plus ceftazidime/avibactam plus high doses of nebulized colistimethate sodium). Evolution of the disease was complicated by multiple organ system dysfunction. Finally, clinical improvement and microbiological cure was achieved.